Strawman arguments and flawed inferences: A response to Naha et al. (January 2021) - Puri, Mahi; Srivathsa, Arjun; Karanth, Krithi K.; Patel, Imran; Samba Kumar, N.
Abstract: Our study titled "The balancing act: Maintaining leopard-wild prey equilibrium could offer economic benefits to people in a shared forest landscape of central India" used an occupancy framework to provide baseline information on patterns and determinants of leopard occurrence and conflict in a human-dominated landscape. We also examined the role of wild prey in offsetting livestock depredation based on leopard diet. In their letter to the Editor, Naha et al. raise concerns about our study, claiming that our methods are inaccurate, and that our inferences are exaggerated. Here, we provide detailed responses to the issues raised by the authors, as we do not find any merits in their claims and reiterate the accurate interpretations of our findings.